2017
DOI: 10.1038/nature21070
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies organogenesis generates autologous functional islets

Abstract: Islet transplantation is an established therapy for diabetes. We have previously shown that rat pancreata can be created from rat pluripotent stem cells (PSCs) in mice through interspecies blastocyst complementation. Although they were functional and composed of rat-derived cells, the resulting pancreata were of mouse size, rendering them insufficient for isolating the numbers of islets required to treat diabetes in a rat model. Here, by performing the reverse experiment, injecting mouse PSCs into Pdx-1-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
194
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(207 citation statements)
references
References 33 publications
4
194
0
3
Order By: Relevance
“…However, advances in stem cell technology and the identification of master regulators of organ formation have spurred efforts to explore this idea using animal models 130132 . For example, genetic deletion of PDX1 in rats leads to specific loss of the entire pancreas due to a failure to create the embryonic pancreas.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, advances in stem cell technology and the identification of master regulators of organ formation have spurred efforts to explore this idea using animal models 130132 . For example, genetic deletion of PDX1 in rats leads to specific loss of the entire pancreas due to a failure to create the embryonic pancreas.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Thus, a mouse pancreas was grown in the body of a rat. The mouse islets from these rats can be harvested and transplanted back to diabetic mice to cure their diabetes 132 . This proof-of-concept experiment between two distinct rodent species provided a glimpse of what the future might hold for growing human organs in animal species.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…However, in both cases, the frequency of chimeric embryos among all injected embryos was remarkably low, and the degree of chimerism -the contribution of the PSC-derived cells to the chimera -was far below the level found in mouse-rat interspecies chimera (Kobayashi et al, 2010;Isotani et al, 2011;Yamaguchi et al, 2017;Wu et al, 2017). Other groups have reported that engrafted human naïve-like PSCs disappear after implantation, or in some cases survive but contribute only to the extraembryonic region (Takashima et al, 2014;Masaki et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…People who receive xenotranplants (e.g., porcine heart valves) are not generally considered less than or other than human, but that view might not apply to, say, neural regeneration. While it is now possible to grow human organs in animals for transplantation (6, 7), in practice, outside of the CNS, most concerns with grafts between species deal with the passage of viruses to the human patients and outlawing the grafting of human ‘reproductive’ cells into animals. In the end, human beings may be forced to answer the question whether being human is what is important or rather continuing to be a person possessed of certain morally valuable traits, such as the ability to love and to be compassionate – recognizing that some humans can lack these traits as well.…”
mentioning
confidence: 99%